1972
DOI: 10.1073/pnas.69.1.162
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitory Protein of Escherichia coli RNA Polymerase in Bacteriophage T3-Infected Cells

Abstract: A partially purified protein isolated from bacteriophage T3-infected cells of Escherichia coli B markedly inhibits the activity of E. coli RNA polymerase, slightly inhibits the activity of purified T3 polymerase, and does not inhibit the activity of either core polymerase or the ribosome-bound T3 polymerase. DEAE-cellulose column (2.2 X 20 cm), which was washed with 150 ml of buffer A; the column was eluted with a gradient from 0 to 0.4 M KCl in buffer A. 5-ml fractions were collected, and the fractions contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…We have previously reported the isolation of an inhibitory protein of Escherichia coli RNA polymerase from E. coli B cells infected with T3 phage, which may be responsible for the arrest of host RNA synthesis (4). During that study we observed that the total activity of host RNA polymerase from T3-infected cells freed from the inhibitory protein and nucleases was considerably lower than the activity of RNA polymerase isolated from uninfected cells.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…We have previously reported the isolation of an inhibitory protein of Escherichia coli RNA polymerase from E. coli B cells infected with T3 phage, which may be responsible for the arrest of host RNA synthesis (4). During that study we observed that the total activity of host RNA polymerase from T3-infected cells freed from the inhibitory protein and nucleases was considerably lower than the activity of RNA polymerase isolated from uninfected cells.…”
mentioning
confidence: 72%
“…% Stimulation is defined as the difference in the activity of combined enzymes (line 3) and that of normal holoenzyme alone (line 1) compared to that of core enzyme alone (line 2). 4. Na dodecyl sulfate-5% polyacrylamide-gel electrophoretogram of ,x' and fi subunits of normal (A) and modified holopolymerases (B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not seem to be the case. In contrast to the T7 repressor, the T3 inhibitor appears to be a late protein, as indicated by the time of induction in vivo (16). It was shown that prior infection with either UVirradiated T3 or with T3 gene-1 mutants-which still could induce the early proteins, except for the gene-1 productdid not reduce significantly phage T4 development.…”
Section: Regulation Of Host Enzymesmentioning
confidence: 99%
“…Recently, an inhibitor of transcription in T3-infected cells was described (16). Since T3 is related to T7, one could imagine that this T3 inhibitor might be closely related to the T7 repressor.…”
Section: Regulation Of Host Enzymesmentioning
confidence: 99%